A model of physical readaptation of combat veterans and members of their families - Glazkova, G.B.; Dubrov, A.A.; Davydova, Yu.A.; Lebedeva, N.V. (Theory and Practice of Physical Culture, 2026)
Objective of the study is the theoretical substantiation of a model of physical readaptation of combat veterans (CV) and members of their families. Methods and structure of the study. In the scientific work carried out at the Plekhanov Russian University of Economics, an analysis, synthesis and generalisation of the literature were conducted; modelling and a scientific and methodological substantiation of the physical readaptation of CV and members of their families were carried out; and conclusions were formulated. Results and conclusions. The physical readaptation of CV and members of their families is a biopsychosocial process using the means of adaptive physical culture (APC), comprising restorative, socio-psychological and family-centred components. The model of physical readaptation has been developed on the basis of biopsychosocial, systemic, activity-based and family-centred approaches. Strategies of readaptation for the target groups of veterans and members of their families have been identified. The structure of the model includes the following levels: individual physical readaptation, family physical readaptation and the institutional organisation of physical readaptation. The effectiveness of the model is evaluated by the following criteria: physical, psychological and social. The model of physical readaptation of CV and members of their families makes it possible to develop 'biopsychosocial' programmes using the means of APC and sport in order to form a family sporting lifestyle and to ensure the successful resocialisation of the target groups into peaceful society.